2017
DOI: 10.21714/1984-6975faces2017v16n4art4553
|View full text |Cite
|
Sign up to set email alerts
|

A Evolução da Ambidestria Internacional nas Pequenas e Médias Empresas (PMES)

Abstract: RESUMOO trabalho apresenta a relação do grau de internacionalização (GRI), da ambidestria internacional e do desempenho organizacional em pequenas e médias empresas (PMEs) exportadoras brasileiras. Ressalta a importância da ambidestria internacional nas capacidades das empresas. Por meio de uma survey em 138 PMEs brasileiras a pesquisa verificou as relações dos três construtos no campo dos negócios internacionais. Esta pesquisa utilizou a técnica do Modelo de Equações Estruturais para a análise, com o método d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…Thus, it managed to make decisions that promoted the development of dynamic capabilities and indirect benefits, such as customer loyalty, impacting the value chain on the economic dimension. It was found that the capabilities of exploitation and exploration formed an international ambidexterity of the company's managers that was identified through routines and organizational processes and that created a sustainable value chain for the company (March, 1991; Moura and Floriani, 2017a, 2017b). The differentiated cooperation capability and the flexibility to deliver a personalized service have led Alpha to build renewable capabilities in its sustainable value chain.…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it managed to make decisions that promoted the development of dynamic capabilities and indirect benefits, such as customer loyalty, impacting the value chain on the economic dimension. It was found that the capabilities of exploitation and exploration formed an international ambidexterity of the company's managers that was identified through routines and organizational processes and that created a sustainable value chain for the company (March, 1991; Moura and Floriani, 2017a, 2017b). The differentiated cooperation capability and the flexibility to deliver a personalized service have led Alpha to build renewable capabilities in its sustainable value chain.…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
“…It was seen that the company develops the exploration capability more than the exploitation capability (Moura and Floriani, 2017a, 2017b). Contact with suppliers of the chain – producers, service providers, transportation, shipping agents and internal associates – enables it to visualize skills to be discovered, exploring new opportunities in the supply chain and developing the social dimension of the value chain.…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
“…When analyzed individually, the exploration and exploitation dimensions are neglected (Severgnini, Galdamez & Vieira, 2019). This empirical gap has encouraged Brazilian researchers and academics to investigate the effect of ambidexterity dimensions on organizational performance (Marques & Silveira-Martins, 2017;Moura & Floriani, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Guerra and Camargo (2021) suggest the need to develop new skills and organizational competencies, aiming to strengthen structures and mechanisms related to organizational ambidexterity and its dimensions, especially in environments of uncertainty. Internationalization has a positive effect on the organizational performance of small and medium-sized enterprises -SMEs (Moura & Floriani, 2017). Albuquerque Filho et al (2021) show that the effect of internationalization on the financial performance of Brazilian and European companies is enhanced when associated simultaneously with innovation activities.…”
Section: Introductionmentioning
confidence: 99%
“…A capacidade de exploitation refere-se à utilização de recursos tangíveis e intangíveis da instituição, ou de terceiros ligados à atividade principal do negócio (POPADIUK, 2015), assim como ao conhecimento agregado às tecnologias já existentes na empresa, assim como no domínio de seus produtos e estratégias de mercado (HE;WONG, 2004;MOURA;FLORIANI, 2017). Sua essência é o refinamento e a extensão de competências tecnológicas (MARCH, 1991), além do aperfeiçoamento do conhecimento, de recursos e resultados (VOGEL; GUTTEL, 2013).…”
Section: Introductionunclassified